Current status of the problem of cardiovascular diseases in the Nizhny Novgorod region: possible ways to reduce mortality - N. Yu. Borovkova; A. S. Tokareva; N. N. Savitskaya; K. I. Krisanova; V. K. Kurashin; G. A. Odintsov (Российский кардиологический журнал, 2022)
The article considers the urgent problem of combating cardiovascular diseases (CVDs) in the Nizhny Novgorod region, including the high prevalence of CVDs and the timely identification of risk factors. The changes in mortality from all and individual causes was analyzed. Attention was paid to the negative impact of the coronavirus disease 2019 (COVID-19) pandemic on the health of people suffering from noncommunicable diseases. We also described the necessity to improve healthcare efficiency for CVD patients by improving the complex of managerial and preventive measures.